Peran Kepemimpinan Strategis dalam Membangun Budaya Organisasi yang Resilien terhadap Teknologi di Lingkungan TNI Guna Menjaga Kedaulatan Negara - Anadi, Andi Nur (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
The advancement of modern defense technology requires the Indonesian National Armed Forces (TNI) to swiftly adapt in order to safeguard national sovereignty. However, limited budgets for education and training pose a significant challenge in enhancing personnel competencies in operating and maintaining advanced technologies. This study aims to examine the role of strategic leadership in building a resilient organizational culture within TNI as a response to technological developments. The method employed is a qualitative literature review, collecting and analyzing secondary data from relevant literature, reports, and policy documents. The findings indicate that strategic leadership plays a critical role in creating adaptive training strategies, integrating modern technology with traditional assets, and overcoming resource constraints through human resource development innovation. A resilient organizational culture and adaptive leadership are essential to improve operational readiness and maintain TNI's strategic advantage in an era of rapid global change. The study's implications highlight the necessity of leadership and training innovation to support sustainable defense reform.